The Political Economy of Fiscal Deficits and Government Production - Gisle James Natvik (Norges Bank, 2009)
This paper analyzes a framework where policymakers decide how to spend public resources on physical capital and labor in order to produce two public goods. Candidate policymakers disagree about which goods to produce, and may alternate in office due to elections. When capital and labor are complementary inputs to the production of public goods, the anticipation of political turnover reduces public savings in physical capital rather than financial assets. Political turnover renders the stock of physical capital for public production too low and inefficiently combined with labor.
hdl:11250/2497637
Keywords: E6; H4; H54; H6; 330; political economics; budget deficits; public investment